De las raíces a la modernidad producción de un EP de cuatro temas fusionando música electrónica con sanjuanito, utilizando instrumentos andinos típicos del sanjuanito imbabureño - Gómez Nazareno, Jairo Yaroslav (2018)
For the reader's understanding, this research project is structured as follows: It starts by describing the contextual framework, the research topic that will be addressed, the objectives, the theoretical framework, the explanation, and the execution and development of the proposal and the results obtained from it. The first chapter refers to the theoretical framework of the traditional Ecuadorian genre of Sanjuanito. It’s concept and origins were analyzed, the first findings of indigenous music in Ecuador. In the same way, how it evolves and subdivides, analyzing its main characteristics. In addition, the chapter points out and explains some of the typical Andean instruments of the Sanjuanito imbabureño that will be used in this research. The second chapter is focused on the study of electronic music. Its origins, the first musical instruments, and its evolution, thus reaching to talk about the two rhythms of this genre (Deep House and Downtempo) that will be used in the development of this project. Subsequently, it explains the influence of electronic music around the world, and how it has managed to merge with the native genres of other countries. The third chapter, the merge of Sanjuanito with Deep house and Downtempo was proposed using typical Andean instruments of the Sanjuanito imbabureño, for which it was carried out with the production of an EP of four songs with the knowledge acquired in the previous chapters. Subsequently, each of the parts of the pre-production, production and post-production process of each song is detailed. Finally, the author puts to consideration the references used in the research